Two Generations — Two Interpretations of Mikhail Bulgakov’s Novel The Master and Margarita - Shimonova, N. V (Телекинет)
The article is a study of the features of the film adaptations of Mikhail Bulgakov’s novel The Master and Margarita using the example of a comparative analysis of Vladimir Bortko’s TV series The Master and Margarita (2005) and Mikhail Lokshin’s film The Master and Margarita (2024). The film adaptation is still one of the main tenors of cinema. The possibility to transfer a literary work to the screen allows the director to express his point of view, enter into a discussion, and draw parallels with modernity. Bulgakov’s work, which had the direct influence of Nikolai Gogol’s prose combining the real and the fantastic, captured his contemporary era both in the mentioned themes and in artistic images. Grotesque, bold experiment, free construction of one’s own artistic space, which reflected not only the originality of the contemporary art world, but also captured the era in all its contradictions and painful problems, elements of science fiction,— all this was reflected in the writer’s work and in one form or another inevitably became part of the film adaptation. In Bulgakov’s work, directors have always been interested in the tragedy of power, the tragedy of the artist, the juxtaposition of freedom and lack of freedom, the problem of choice, etc. These themes and conflicts do not belong to one era or one country alone, but go beyond narrowly focused conflicts.